Simultaneous production of rhamnolipids, 2-alkyl-4-hydroxyquinolines, and phenazines by clinical isolates of Pseudomonas aeruginosa. - Smeal, B C (J Clin Microbiol, 1987)
Of 72 clinical isolates of Pseudomonas aeruginosa examined for simultaneous production of secondary metabolites, 86% produced 2-alkyl-4-hydroxyquinolines, 75% produced rhamnolipids, and 58% produced phenazines, including pyocyanin. Whereas isolates producing two or one constituted smaller groups, 39% released all three metabolites. Metabolite production did not appear to influence site of infection.